2003
DOI: 10.1046/j.1532-5415.2003.51060.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality‐Related Factors and 1‐Year Survival in Nursing Home Residents

Abstract: MDS data can identify major factors associated with 1-year mortality in newly admitted and long-stay nursing home residents. These factors can be used to stratify residents into risk categories for 1-year mortality. This information could be important to residents, their families, and their physicians when developing care plans, as well as to agencies interested in healthcare resource planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
102
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(118 citation statements)
references
References 22 publications
11
102
0
5
Order By: Relevance
“…En suma, un número significativo de AM pobres institucionalizados se encuentra con importantes alteraciones funcionales por lo tanto con gran fragilidad, lo que es un factor de mayor costo de atención (humano y económico), incluso de mortalidad a un año plazo 3,14,15 . Lo anterior tiene…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En suma, un número significativo de AM pobres institucionalizados se encuentra con importantes alteraciones funcionales por lo tanto con gran fragilidad, lo que es un factor de mayor costo de atención (humano y económico), incluso de mortalidad a un año plazo 3,14,15 . Lo anterior tiene…”
Section: Discussionunclassified
“…Este es el primer estudio de población de AM residentes en instituciones en nuestro país y entendemos que nuestros resultados son importantes para la planificación de estrategias de intervención, reordenamiento y asignación de recursos humanos y económicos, con el fin de mejorar la calidad de vida, poniendo énfasis en áreas como la prevención de discapacidad y rehabilitación, áreas que mejoran la funcionalidad del AM 15 .…”
Section: A R T í C U L O D E I N V E S T I G a C I ó Nunclassified
“…In addition, a recent meta-analysis concluded that none of the prediction models are ready for use in clinical practice, because their validity has not been tested in other populations (15). Another limitation of the existing prediction models is the need for laboratory tests, which increases the costs and reduces the feasibility of using them in developing countries (10,12,19,20). In addition, most models predict mortality for 5 years and may not be adequate for making decisions about chronic disease care such as cancer screening and treatment that may only affect long-term risk (eg, bisphosphonates) (10,12).…”
mentioning
confidence: 99%
“…Another limitation of the existing prediction models is the need for laboratory tests, which increases the costs and reduces the feasibility of using them in developing countries (10,12,19,20). In addition, most models predict mortality for 5 years and may not be adequate for making decisions about chronic disease care such as cancer screening and treatment that may only affect long-term risk (eg, bisphosphonates) (10,12). To overcome these limitations, we developed and validated a 10-year prediction model for mortality in adults aged 60 years and older, using data from 16 …”
mentioning
confidence: 99%
See 1 more Smart Citation